Evaluation of Hygiene and Sanitation Catering in Gayungsari Surabaya Street - Yenni Suryansyah (Universitas Airlangga, 2018)
Hygiene and sanitary food service is one of the mandatory food safety in catering, it is very important to be applied to maintain the health of consumers. The purpose of this study was to evaluate the hygiene and sanitation of catering in Gayungsari street Surabaya. This was an evaluative study with cross sectional design. The research object consisted of two parts, namely the production area and food handlers, the amount of the total population were 30 food handlers. Variables for the production area were processing area and production process, while the variables for food handlers were food handlers's health and their behaviour. This study used three methods for assessment, namely, observation, interview and rectal swab. The result of this research were the catering was good, because it met the standards of the Ministry of Health Regulation No. 1096 of 2011 on Hygiene and Sanitation Catering, but the lighting in the production area was still less than the standard, and there is one employee who detected E. coli excess in the body on examination of rectal swabs. Suggestions for the catering, rectal swabs and medical examinations should be done regularly to all food handlers, and also the addition of lights in the area of production, because the food handlers need bright enough lighting at work.